Ecology of Rafflesia arnoldii (Rafflesiaceae) in Pandam Gadang West Sumatra - Syafroni Pranata; Sulistijorini Sulistijorini; Tatik Chikmawati (Journal of Tropical Life Science, 2019)
Pandam Gadang has tropical forests which become the habitat of Rafflesia (Rafflesia arnoldii) which grows as a parasite of Tetrastigma (Vitaceae). Study on R. arnoldii is needed since its population continuously decrease as a result of habitat destruction of its host. The aim of the study was to determine habitat conditions, vegetation structure, and characteristic of the host species of Rafflesia; to identify environmental factors, and determine the Rafflesia habitat suitability in Pandam Gadang Koto Tinggi Village, West Sumatra. Analysis of vegetation in the habitat where Rafflesia grows using a circular plot. The number of individuals Rafflesia found was recorded and completed with observations of its morphology. Micro-climate measurements were carried out together with data collection in the field. Flower morphological analysis was descriptively presented. Environmental parameters were-processed with Canoco software 4.56 using Canonical Correspondence Analysis. Habitat suitability was analyzed using Maximum Entropy. The 17 Rafflesia individuals found on Pandam Gadang were R. arnoldii, known as